Integrasi Pengabdian Kepada Masyarakat Berbasis Warga Binaan Lapas Kelas IIA Kendal - Sugiharto, Prasetyawan Aji; Santoso, Yan Imam; Najib, Muhammad Reza Ainun; Shofyana, Maila Huda; Aditama, Madya Giri; Mubarak, Zaky (TRIMAS: Jurnal Inovasi dan Pengabdian Kepada Masyarakat, 2024)
Efforts to build character through education are the right of every citizen to obtain education. The educational movement in prisons (correctional institutions) aims to strengthen the character of inmates through harmonization of heart (ethics), sense (aesthetics), thought (literacy) and sports (kinesthetics) with the support of public involvement and collaboration between educational institutions. Apart from that, it equips inmates to face conditions of moral, ethical and character degradation. The method of community service activities is through lectures and outreach to the target residents regarding religious aspects, educational aspects, legal aspects and health aspects. This community service activity was carried out on June 6 2024 at the Kendal Class IIA Correctional Institution. With this activity, prison inmates can strengthen their religious aspects so that they are able to correct mistakes and behave well, become citizens based on the character values ​​of the Indonesian nation, can know their rights as legal prisoners and lead a healthy life in body and soul.